Accessing Bisphosphine Copper(I) Complexes with Recalcitrant Pterin–Phenanthroline Ligands Through Mechanochemistry - Siva S. M. Bandaru; Christian Fischer; Jevy V. Correia; Anna-Lena Land; Carola Schulzke (Inorganics, 2025)
The synthesis of [Cu(PteN˄N)(P˄P)][BF4] complexes with pterin-fused phenanthroline (PteN˄N) derivatives and bisphosphine (P˄P) co-ligands was achieved through a mechanochemical approach. Due to the extremely poor solubility of PteN˄N ligands, traditional solution methods are ineffective, whereas solid-state mechanochemistry reliably yielded the targeted heteroleptic—rather than homoleptic—complexes with considerable stability even in solution. The transformation from ligand to complex increased the solubility dramatically. The ligands and complexes were comprehensively characterised with a mixture of routine spectroscopic and spectrometric methods, the applicability of which depended to some extent on the compounds’ solubility, e.g., in the case of NMR spectroscopy. The photophysical properties of the complexes, which were not as exciting as anticipated, were assessed by absorption and emission spectroscopic methods, showing that further improvements are needed in complex design if these species are to be developed towards photocatalysis in the future.